Systematic Literature Review: Pengaruh Frekuensi Olahraga terhadap Tingkat Stres pada Karyawan - Fardli Hamdani Kurniawan; Neneng Sofiyanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Abstract: Work-related stress is a crucial issue in modern organizational settings, significantly affecting employees’ psychological well-being and overall company productivity. Physical exercise is widely recognized as an effective coping mechanism for reducing stress; however, there remains a lack of clarity regarding its optimal frequency in a managerial context. This study aims to systematically review national scholarly literature concerning the impact of exercise frequency on employee stress levels. The method employed is a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol. Articles were retrieved from the Google Scholar database using inclusion criteria: studies that investigated the variables of exercise frequency and occupational stress among Indonesian employees, published between 2020–2025, and available in full-text format. From 189 initial articles, 10 were selected following screening and quality assessment procedures. The synthesis reveals that regular exercise (3–5 times per week) significantly reduces stress, enhances emotional balance, and strengthens psychological resilience. Exercise also functions as a personal resource within the Job Demands-Resources (JD-R) model and as a form of problem-focused coping in managing occupational stress. These findings underscore the need for organizational support through evidence-based health policies. It is recommended that companies design and integrate structured physical activity programs as part of long-term stress management strategies in the workplace.